2018
DOI: 10.1186/s13045-018-0585-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of ruxolitinib versus best available therapy on bone marrow fibrosis in patients with myelofibrosis

Abstract: BackgroundMyelofibrosis (MF) is a life-shortening complication of myeloproliferative neoplasms associated with ineffective hematopoiesis, splenomegaly, and progressive bone marrow (BM) fibrosis. The oral Janus kinase (JAK) 1/JAK2 inhibitor ruxolitinib has been shown to improve splenomegaly, symptom burden, and overall survival in patients with intermediate-2 or high-risk MF compared with placebo or best available therapy (BAT).MethodsThe effects of ruxolitinib therapy for up to 66 months on BM morphology in 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 55 publications
(77 reference statements)
1
54
0
3
Order By: Relevance
“…In clinical trials, ruxolitinib was shown to significantly reduce spleen size, ameliorate debilitating MF-related symptoms, and improve QoL in patients with intermediate-2 or high-risk MF versus best available treatment, with overall survival also improved versus placebo [38,39]. The benefits of ruxolitinib on spleen size and overall survival have been shown to be maintained over longer-term therapy [40,41], and sustained treatment was also associated with greater odds of bone marrow fibrosis improvement or stabilization and decreased odds of bone marrow fibrosis worsening in a large proportion of patients with MF versus best available treatment [42]. Additionally, ruxolitinib has demonstrated significant reductions in spleen size, control of haematocrit, and improvement of PV-related symptoms.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…In clinical trials, ruxolitinib was shown to significantly reduce spleen size, ameliorate debilitating MF-related symptoms, and improve QoL in patients with intermediate-2 or high-risk MF versus best available treatment, with overall survival also improved versus placebo [38,39]. The benefits of ruxolitinib on spleen size and overall survival have been shown to be maintained over longer-term therapy [40,41], and sustained treatment was also associated with greater odds of bone marrow fibrosis improvement or stabilization and decreased odds of bone marrow fibrosis worsening in a large proportion of patients with MF versus best available treatment [42]. Additionally, ruxolitinib has demonstrated significant reductions in spleen size, control of haematocrit, and improvement of PV-related symptoms.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…In addition, a possible effect of ruxolitinib on bone marrow fibrosis has been reported in both clinical studies [14] and in real-life experience [15-17]. …”
Section: Discussionmentioning
confidence: 99%
“…BCR-ABL tyrosine kinase inhibitors (TKI) have fundamentally changed the therapeutic paradigm of chronic myeloid leukemia (CML) and possibly of ALL with BCR-ABL mutations in the near future [22,23]. JAK2 inhibitors, ruxolitinib and fedratinib, are major therapy options for myelofibrosis [24][25][26]. Inhibitors for BCL-2, venetoclax, and Bruton tyrosine kinase, ibrutinib and acalabrutinib, are playing major roles in therapy for chronic lymphoid leukemia as well as in mantle cell lymphoma [27][28][29][30].…”
Section: Small Molecule Inhibitors (Smi) As Targeted Agents: Small Pimentioning
confidence: 99%